1.化简求值3x^2-2y^2+(y^2-2x^2)-(6x^2-y^2),其中x=-2,y=3.2(2x^3-6x-4

3个回答

  • 1.化简求值

    3x^2-2y^2+(y^2-2x^2)-(6x^2-y^2),其中x=-2,y=3.原式=-5x^2=(-5)x(-2)^2=-20

    2(2x^3-6x-4)-3(x^3+x^2-2x-3),其中x=-2/3原式=-x^3-3x^2+5=(8/27)-(4/3)+5=(-28/27)+5=107/27

    第2题

    已知a+b=2,ab=-1,求(4a-5b-ab)-(2a-7b+5ab)的值原式=2a+2b-6ab=2(a+b)-6ab=2x2-6x(-1)=10

    第3题

    若式子(2x^2+ax-y+6)-(abx^2-3x+5y-1)的值与字母x的值无关,求式子1/2a^2-2b+4ab的值(2x^2+ax-y+6)-(abx^2-3x+5y-1)=(2-ab)x^2+(a+3)x-6y+7;要使此式与x无关,必须 2-ab=0且a+3=0解得 a=-3,b=(-2/3)所以 1/2a^2-2b+4ab=(9/2)+(4/3)+8=83/6